(untitled) (Medical Forum Monthly, 2024)
Introduction: Medicolegal autopsies can be valuable source of data on ascertainment of specific causes of reported deaths, particularly homicides in a particular geographic area. The present study provides information regarding the medicolegal deaths which autopsied in Quetta Balochistan. Objectives: The aim of this study is to analysis the pattern of injuries, age group, gender, causative agent, cause and manner of medicolegal death found on autopsies of Quetta and its suburbs that follows the traditional pattern of life and considers as a backward society. Study Design: Retrospective study of Medico Legal autopsies referred by police for complete medicolegal autopsy at Police Surgeon medicolegal department of Sandeman Civil Hospital, Quetta Balochistan. Place and Duration of Study: This study was conducted at Medicolegal Department of Sandeman Civil Hospital Quetta from 1st January 2006 to 31st December 2008. Materials and Methods: The present study is based on record of 122 medicolegal deaths autopsied during the study period in the mortuary of Sandeman Civil Hospital Quetta affiliated with Bolan Medical College Quetta from 1st January 2006 to 31st December 2008. Results: Out of 122 medicolegal autopsies Males accounted for 90.16% and Females were 9.84%. Male: female ratio 9.16:1. The majority cases 45 (36.88%) were in the age group of 20-29 years followed by 34 (27.86%) cases in age group of 30-39 years. Most common cause of deaths in majority of cases was firearm 59 (48.36%), bomb blast explosions 12 (9.83%), sharp force injuries 9 (07.38%), blunt injuries 5 (04.10%), burn 4(03.28%). Homicidal deaths constituted 90 (73.77%), accidental deaths (9.84%), suicidal 3 (2.46%), undetermined 2 (01.64%) and natural deaths 15 (12.29%). The head and trunk is most affected area in cases of physical trauma Conclusion: study concludes that homicidal deaths by firearms were observed in majority of medicolegal deaths.